Competition, Rivalries, and the Tall Poppy Syndrome in Medicine and Orthopedics - Douglas E Garland (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2018)
Social comparisons, although often subconscious, contribute to defining who we are. We constantly compare ourselves to new acquaintances, neighbors, friends (often through social media), professional colleagues, and people in the media. Comparison allows us to identify ourselves: our self image, intellectual and physical abilities, and financial and social standing.